(untitled) (Res Medica, 2014)
19th century and early 20th century physicians taught their students: “Know syphilis and you will know medicine.” In this last decade of the 20th century, physicians could justifiably substitute the word ‘AIDS’ for ‘syphilis’. Every aspect of human immunodeficiency virus (HIV) infection - whether the epidemiology, immunology, pathogenesis, diagnosis, management or prevention - presents an intellectual challenge to our profession. Politicians, educationalists, doctors and the lay public ignore this disease at their peril. We all have a duty to ourselves and to future generations to do everything possible to control and ultimately to eliminate HIV infection.